Costimulation of γδTCR and TLR7/8 promotes Vδ2 T-cell antitumor activity by modulating mTOR pathway and APC function. Issue 12 (22nd December 2021) - Wang, Huaishan; Chen, Hui; Liu, Shujing; Zhang, Jie; Lu, Hezhe; Somasundaram, Rajasekharan; Choi, Robin; Zhang, Gao; Ou, Lingling; Scholler, John; Tian, Shifu; Dong, Liyun; et al.
Abstract : Background: Gamma delta (γδ) T cells are attractive effector cells for cancer immunotherapy. Vδ2 T cells expanded by zoledronic acid (ZOL) are the most commonly used γδ T cells for adoptive cell therapy. However, adoptive transfer of the expanded Vδ2 T cells has limited clinical efficacy. Methods: We developed a costimulation method for expansion of Vδ2 T cells in PBMCs by activating γδ T-cell receptor (γδTCR) and Toll-like receptor (TLR) 7/8 using isopentenyl pyrophosphate (IPP) and resiquimod, respectively, and tested the functional markers and antitumoral effects in vitro two-dimensional two-dimensional and three-dimensional spheroid models and in vivo models. Single-cell sequencing dataset analysis and reverse-phase protein array were employed for mechanistic studies. Results: We find that Vδ2 T cells expanded by IPP plus resiquimod showed significantly increased cytotoxicity to tumor cells with lower programmed cell death protein 1 (PD-1) expression than Vδ2 T cells expanded by IPP or ZOL. Mechanistically, the costimulation enhanced the activation of the phosphatidylinositol 3-kinase (PI3K)–protein kinase B (PKB/Akt)–the mammalian target of rapamycin (mTOR) pathway and the TLR7/8–MyD88 pathway. Resiquimod stimulated Vδ2 T-cell expansion in both antigen presenting cell dependent and independent manners. In addition, resiquimod decreased the number of adherent inhibitory antigen-presenting cells (APCs) and suppressed the inhibitory function of APCs by decreasing PD-L1 and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) expression in these cells during in vitro Vδ2 T-cell expansion. Finally, we showed that human Vδ2 T cells can be expanded from PBMCs and spleen of humanized NSG mice using IPP plus resiquimod or ZOL, demonstrating that humanized mice are a promising preclinical model for studying human γδ T-cell development and function. Conclusions: Vδ2 T cells expanded by IPP and resiquimod demonstrate improved anti-tumor function and have the potential to increase the efficacy of γδ T cell-based therapies.